NONCLASSICAL FOURTH ORDER DISCONTINUOUS BOUNDARY VALUE PROBLEM WITH ABSTRACT LINEAR FUNCTIONALS - KANDEMÄ°R, Mustafa (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this study, we have considered a nonstandard boundary-value problem for fourth order differential equation on two disjoint intervals The boundary conditions contains not only endpoints and but also a point interaction and abstract linear functional So our problem is nota pure differential one. We investigate such some important properties as isomorphism, Fredholmness and coerciveness with respect to the spectral parameter.